2017
DOI: 10.3390/molecules23010009
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Nanoparticles in the Central Nervous System: Targeting Principles, Applications and Safety Issues

Abstract: One of the most challenging goals in pharmacological research is overcoming the Blood Brain Barrier (BBB) to deliver drugs to the Central Nervous System (CNS). The use of physical means, such as steady and alternating magnetic fields to drive nanocarriers with proper magnetic characteristics may prove to be a useful strategy. The present review aims at providing an up-to-date picture of the applications of magnetic-driven nanotheranostics agents to the CNS. Although well consolidated on physical ground, some o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 94 publications
(255 reference statements)
0
68
0
Order By: Relevance
“…Different inorganic nanoparticular carriers have been applied in this field, e.g. iron oxide, cerium oxide, molybdenum, silica or gold nanoparticles [40][41][42][43][44] . Compared to other types of nanoparticles, gold nanoparticles have received considerable www.nature.com/scientificreports/ interest because of their relative low cytotoxicity, predominant optical properties for imaging, well-established syntheses, and their potential to cross the BBB 14,28,45,46 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different inorganic nanoparticular carriers have been applied in this field, e.g. iron oxide, cerium oxide, molybdenum, silica or gold nanoparticles [40][41][42][43][44] . Compared to other types of nanoparticles, gold nanoparticles have received considerable www.nature.com/scientificreports/ interest because of their relative low cytotoxicity, predominant optical properties for imaging, well-established syntheses, and their potential to cross the BBB 14,28,45,46 .…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that 2 h after injection, 20 nm gold nanoparticles had a broad biodistribution and a considerable accumulation within the brain. The possibility to apply steady and alternating magnetic fields to drive magnetic nanoparticles and liposomes across the BBB was also shown 21,40,51 .…”
Section: Discussionmentioning
confidence: 99%
“…With combined fluorophore, the position of MNPs could be directly tracked in the brain parenchyma of normal mice, which also allow cellular-level by confocal microscopy. The magnetic nanoparticles could target for extravasation and assembly by apply magnetic field which could be used for crossing BBB drug delivery to treatment of various CNS diseases [ 100 , 101 , 102 ].…”
Section: Research Progress In Methods For Blood–brain Barrier Permmentioning
confidence: 99%
“…However, very few studies have been performed using AgNPs as drug delivery systems as a treatment of CNS neurons, especially due to several safety-related aspects [29][30][31]. But these safety issues are not only associated with AgNPs; in fact, in spite of all of the mentioned advantageous properties of inorganic NPs, the majority still have major drawbacks and have been shown to be particularly critical for the brain, as they can induce neurotoxicity, neuroinflammation and can permanently alter the BBB permeability [23,32,33].…”
Section: Inorganic Nanosystemsmentioning
confidence: 99%